2017
DOI: 10.3389/fpsyg.2017.01176
|View full text |Cite
|
Sign up to set email alerts
|

Possession Zone as a Performance Indicator in Football. The Game of the Best Teams

Abstract: Possession time in football has been widely discussed in research but few studies have analyzed the importance of the field area in which possession occurs. The objective of this study was to identify the existence of significant differences in the field zone of ball possession between successful and unsuccessful teams and to acknowledge if the match status modulates the possession model. To this end, 2,284 attacks were analyzed corresponding to the matches in the final phase of the UEFA Euro 2016 France, reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 38 publications
8
54
1
6
Order By: Relevance
“…Similar findings, but for different leagues, can be found from other studies (Lago-Peñas & Dellal , 2010;Armatas, Zaggelidis, Skoufas, Papadopoulou, & Fragkos, 2009;GÖRAL, 2015;Kempe, Vogelbein, Memmert, & Nopp, 2014;Aquino, Garganta, Manechini, Bedo, & Puggina, 2017). Moreover, for possession to be effective, it must happen closer to your opponent's goal; otherwise, an increase in possession is totally ineffective (Casal, Maneiro, Ardá, Marí, & Losada, 2017).…”
Section: Literature Reviewsupporting
confidence: 78%
“…Similar findings, but for different leagues, can be found from other studies (Lago-Peñas & Dellal , 2010;Armatas, Zaggelidis, Skoufas, Papadopoulou, & Fragkos, 2009;GÖRAL, 2015;Kempe, Vogelbein, Memmert, & Nopp, 2014;Aquino, Garganta, Manechini, Bedo, & Puggina, 2017). Moreover, for possession to be effective, it must happen closer to your opponent's goal; otherwise, an increase in possession is totally ineffective (Casal, Maneiro, Ardá, Marí, & Losada, 2017).…”
Section: Literature Reviewsupporting
confidence: 78%
“…Numerous examples have been described in the literature, particularly in recent years, and have been applied to a wide range of sporting contexts, including motor skill analysis (Castañer et al, 2009), physical activity (Castañer et al, 2016b), middle- and long-distance races (Aragón et al, 2015, 2017), basketball (Fernández et al, 2009), soccer (Jonsson et al, 2006; Castañer et al, 2016a, 2017a; Casal et al, 2017; Diana et al, 2017), judo (Gutiérrez-Santiago et al, 2011), hockey (Hernández-Mendo and Anguera, 2002), futsal (Lapresa et al, 2013b), and kinesics (Castañer et al, 2013). Ad-hoc instruments have been shown to be equally effective in amateur (Arana et al, 2013) and elite (Barreira et al, 2014) sport.…”
Section: Inclusion Of Purely Observational Sports and Physical Activimentioning
confidence: 99%
“…Taking the variable "ball possession" in isolation, preliminary studies have shown that the best teams maintained a higher percentage of ball possession during the matches, and that their game pattern was more stable (Lago-Peñas and Dellal, 2010). In addition, the local teams have more possession than the visiting teams (Lago and Martín, 2007), and the ball possession time is greater in the first part in the successful teams (Casal et al, 2017). In addition, the local teams have more ball possession than the visiting teams (Lago and Martín, 2007), and the ball possession time is greater in the first half of the match in successful teams (Casal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the local teams have more possession than the visiting teams (Lago and Martín, 2007), and the ball possession time is greater in the first part in the successful teams (Casal et al, 2017). In addition, the local teams have more ball possession than the visiting teams (Lago and Martín, 2007), and the ball possession time is greater in the first half of the match in successful teams (Casal et al, 2017). It has also been found that successful teams have significantly longer ball possessions than unsuccessful ones (Jones et al, 2004), and that the former maintain this ball possession in the mid-offensive zone, while the unsuccessful ones kept it in the middle defensive zone.…”
Section: Introductionmentioning
confidence: 99%